Effect of corvitin on changes in cytokin levels in the development of experimental bronchial asthma in combination with adrenaline miocardial damage - Nebelyuk, Nazariy (Journal of Education, Health and Sport, 2021)
Bronchial asthma (BA) is a fairly common disease of the bronchopulmonary system. Its share is from 0.6 to 2% of all respiratory pathology, in different countries this pathology affects from 1 to 10% of the population, in general, the world has at least 2% of the total population. Cardiovascular diseases continue to be a serious problem in medicine. The reason for this is a large number of stresses of various origins, which cause disruption of the body’s adaptive capacity, the development of functional and structural changes in it, which ultimately lead to necrotic myocardial damage. The problem of pathogenesis, early diagnosis and treatment of BA today is not fully understood, it is still one of the serious issues of modern medicine. Despite lengthy research, the serious costs of research, the participation of the world’s leading experts, methods of prevention and treatment of cardiovascular diseases, and rehabilitation of patients remain imperfect, although some progress and serious results have already been achieved. The aim of our study was to find out how cytokine levels will change at different stages of the formation of experimental asthma (EA) and adrenaline myocardial damage (AMD), what will be the indicators in the combination of these pathologies and what will be the effect of Corvitin on disorders combination of EA and AMD. The study was conducted on 127 guinea pigs. Blood sampling was performed on the 1st, 4th, 18th and 25th days of EA development, on the same days in AMD, as well as in combination with EA with AMD, and on the 25th day of development of these diseases with treatment. Corvitin, the level of pro-inflammatory cytokines - tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6) and anti-inflammatory - interleukin-10 (IL-10) was determined by solid-phase enzyme-linked immunosorbent assay. Studies of cytokine levels in different groups of animals (intact, with EA, with AMD, with EA and AMD and in animals after treatment) showed that in animals with diseases, the rate of pro-inflammatory IL-6 and TNF-α increased with decreasing IL-10. At a combination of pathologies changes were the greatest that testifies to a course of diseases more difficult for an organism. The use of Corvitin showed a positive effect on the violation of cytokine levels and their imbalance, which was due to its antioxidant, anti-inflammatory and immunomodulatory effects. Therefore, quercetin may be effective in the treatment of asthma or a combination of pathologies.